Utilization of e-commerce to increase culinary business opportunities for rural communities - Yoanita Alexandra; Nosica Rizkalla; Septi Fahmi Choirisa; Ringkar Situmorang; Purnamaningsih Purnamaningsih (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2024)
Serdang Wetan Village is one of the villages in Tangerang Selatan, Indonesia which will focus on improving welfare through science and technology, MSMEs and human resource potential. Serdang Wetan village still has several problems, where the level of education is still low, as well as the type of business of the village community which is focused only on the culinary business. The human capital has very limited skills besides local food and beverage production. Thus, it is shown the importance of encouraging job creation in the village through e-commerce media. In this digital world, people are more likely to shop using online media. E-commerce can open up even greater business opportunities, both for culinary businesses and other MSMEs. The training provided is in the form of an introduction to online business (e-commerce) with a focus on social commerce or selling using social media, to tips and tricks for selling using e-commerce. In this training, a technopreneur in the culinary field will also be invited who share her experiences in doing business using the e-commerce platform. Apart from that, following the SDGs, this activity can help village communities to expand business opportunities, so it is hoped that it can help eradicate poverty and hunger, reduce inequality, sustainable consumption, and production as well as partnerships to achieve goals.Â